G. lucidum triterpenes restores intestinal flora balance in non-hepatitis B virus-related hepatocellular carcinoma: evidence of 16S rRNA sequencing and network pharmacology analysis - Wei Xiong; Ce Yang; Jing Xia; Wenxiang Wang; Ning Li (Frontiers Media S.A., 2023)
Background: Ganoderma lucidum (G. lucidum) is a popular traditional remedy medicine used in Asia to promote health and longevity, which has also been highlighted for anti-cancer effects. This study investigated the molecular pharmacological mechanism of G. lucidum triterpenes in influencing intestinal flora imbalance in non-hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) based on 16S rRNA sequencing technology and network pharmacology analysis.Methods: 16S rRNA sequencing data of fecal samples from normal controls and HCC patients were obtained from the SRA database. G. lucidum triterpenes and HCC-related targets were screened by BATMAN-TCM, ETCM, and GeneCards databases. The TCGA-LIHC dataset was downloaded through the TCGA database to analyze the differential expression of key genes. NHBV-related HCC-related transcriptome RNA sequencing dataset was downloaded via the GEO database.Results: Abundance of intestinal flora in the HBV-related HCC and NHBV-related samples was higher than that of control samples. The intestinal flora of NHBV samples was mainly enriched in apoptosis and p53 pathways. Totally, 465 G. lucidum triterpenes-related targets were intersected with 4186 HCC-related targets, yielding 176 intersected targets. Among them, apoptosis and p53 pathway factors were located at the core of the protein-protein interactions network. Ganosporelactone B, the active component of G. lucidum triterpenes, had the lowest binding free energy to CASP3. CASP3 expression were upregulated in HCC tissue samples, and had higher predictive value in NHBV-related HCC patients.Conclusion: Therefore, Ganosporelactone B, the active ingredient of G. lucidum triterpenes, improves the imbalance of intestinal flora and ultimately curtails development of NHBV-related HCC.